A study on sand brick using wood dust as sand replacement - Nurul Nadia, Abdul Karim (2019)
Recently, construction is one of the developing industry, thus the demand for the natural resources in order to produce the mixtures and material is getting high. Due to the limitation of sources and difficulties in production it is lead to the shortage and increasing of price of materials for construction works. Besides that, deal with environmental issues that related to the pollution that cause by the waste product from the industries. Increase in sand usage lead to mining activities that cause the ecological inequality such as degradation and corrosion of river bank. This research focused in term to determine the optimum wood dust as sand replacement material for sand brick production and to examine the compressive strength and water absorption rate. The study has been conducted in three different percentages which is 2.5%, 5.0% and 7.5% of wood dust replacement. Control samples with 0% replacement is use to compare with the other percentages. The mix ratio used for every mixtures is 1:6 and undergo 7 days and 28 days of curing process before the tested can be conducted. Total 80 numbers of brick were prepared with size 225 mm x 115 mm x 75 mm. The distribution of samples was 5 samples for each testing for both 7 days and 28 days for every percentage. The results show that the strength was reduce directly when the percentages of wood dust replacement increase as well as the water absorption rate also increase. The findings also show that the samples with 2.5% of wood dust are higher in compressive strength and lowest water absorption among the other samples.